Football, alcohol and gambling: an unholy trinity? - Carwyn Jones (Karolinum Press, 2016)
In this paper I argue that football plays a questionable role in promoting two potentially problematic activities, namely drinking alcohol and gambling. Gambling and alcohol companies sponsor clubs and competitions and also pay to advertise their products at the stadia and during television coverage. Consequently millions of fans, including children, are exposed to the marketing of these restricted products. The latter are exposed despite regulations that prohibit such advertising and promotion in other contexts. The promotion of these activities to children and to adults increases levels of consumption which in turn increases the number of problem drinkers and gamblers in society. High-profile footballers play a further role in normalising drinking and gambling. They are role models whose actions influence others. Their excessive drinking and gambling activities provide poor examples for football fans, young and old.